Mechanisms of the NAD+ salvage pathway in enhancing skeletal muscle function - Su, Mengzhu; Qiu, Fanghui; Li, Yansong; Che, Tongtong; Li, Ningning; Zhang, Shuangshuang (Frontiers in Cell and Developmental Biology, 2024)
Nicotinamide adenine dinucleotide (NAD + ) is crucial for cellular energy production, serving as a coenzyme in oxidation-reduction reactions. It also supports enzymes involved in processes such as DNA repair, aging, and immune responses. Lower NAD+ levels have been associated with various diseases, highlighting the importance of replenishing NAD+. Nicotinamide phosphoribosyltransferase (NAMPT) plays a critical role in the NAD + salvage pathway, which helps sustain NAD + levels, particularly in high-energy tissues like skeletal muscle.This review explores how the NAMPT-driven NAD+ salvage pathway influences skeletal muscle health and functionality in aging, type 2 diabetes mellitus (T2DM), and skeletal muscle injury. The review offers insights into enhancing the salvage pathway through exercise and NAD+ boosters as strategies to improve muscle performance. The findings suggest significant potential for using this pathway in the diagnosis, monitoring, and treatment of skeletal muscle conditions.